2020
DOI: 10.1093/jas/skaa342
|View full text |Cite
|
Sign up to set email alerts
|

Using near-infrared spectroscopy to determine intramuscular fat and fatty acids of beef applying different prediction approaches

Abstract: This study aimed to predict fat and fatty acids (FA) contents in beef using near-infrared spectroscopy and prediction models based on partial least squares (PLS) and support vector machine regression in radial R-SVR kernel. Fat and FA were assessed in 200 longissimus thoracis samples, and spectra were collected in reflectance mode from ground meat. The analyses were performed for PLS, and R-SVR with and without wavelength selection based on genetic algorithms (GA). The GA application improved the error predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Therefore, these are often not reported and published data tend to focus on the main groups of FA [ 24 , 50 , 52 , 58 ]. Most authors reported worse statistics for PUFA than for SFA and MUFA [ 14 , 48 , 53 , 55 , 59 ]. This could be explained because long-chain PUFA are mainly located in the membrane phospholipids which are quite constant because they are controlled by a complex enzymatic system, providing low variability among animals and have relatively low concentrations [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these are often not reported and published data tend to focus on the main groups of FA [ 24 , 50 , 52 , 58 ]. Most authors reported worse statistics for PUFA than for SFA and MUFA [ 14 , 48 , 53 , 55 , 59 ]. This could be explained because long-chain PUFA are mainly located in the membrane phospholipids which are quite constant because they are controlled by a complex enzymatic system, providing low variability among animals and have relatively low concentrations [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The poor performance of NIRS in prediction equations for FA is due to this low variability and because some FA absorbs at the same wavelengths [ 14 , 47 ]. In our data set the range of variability may result in a complex relationship between the spectra and the response variables that are not predicted under a PLS model [ 59 ]. Using the NIRS technique to predict fatty acids is hampered by the absorption of light by the C–H bonds in certain wavelengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition could generate complex relationships between the spectra and the response variables that are not capable of being predicted under a PLSR model. In fact, Barragán-Hernández et al (2020) considerably improved NIRS predictability of individual and groups of FA in ground beef samples when support vector machine-learning (SVM) regression was applied (R 2 p = 0.74 to 0.99) compared with PLSR (R 2 p = 0.06 to 0.58). Therefore, regression based on SVM could be a novel alternative that manages to identify several vectors in hyperspace capable of constructing a generalizable prediction model for estimating FA profiles in beef with higher accuracy than conventional methods.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…The results showed that the predictive accuracy of the model after screening with the SPA method was higher. In 2020, Barragá n et al [22] used GA (Genetic Algorithm) combined with PLS and Radial Kernel Support Vector Machine Regression (R-SVR) models to predict the fatty acid content in beef. After analysis, it was found that the application of GA increased the error prediction of the two models by 15% and 68% respectively.…”
Section: Introductionmentioning
confidence: 99%